SOYBEAN PERFORMANCE AND CANONIC INTER-RELATIONS TOWARDS SPACING BETWEEN SOWING LINES - Filho, Evaldo Cervieri; Meneghello, Géri Eduardo; Villela, Francisco Amaral; Carvalho, Ivan Ricardo Ricardo; Lautenchleger, Francine; Moura, Natã Balssan (REVISTA DE AGRICULTURA, 2021)
The aimed of study to evaluate soybean performance and canonical interrelationships towards spacing between sowing lines. This study was developed in the 2019/2019 crop season, in the county of Lagoa da Confusão-TO. The experimental design used was randomized blocks with four replications, using five spacing between lines (45, 35, 25 21 and 17 centimeters), conserving the same plant population. The plots consisted of four lines ten meters long. The was 30 cm between rows, demonstrating that it is attractive for soybean sowing. To this end, it should be noted that the reduction in the spacing of the sowing line leads to an increase in costs and operating time, which can make this recommendation unfeasible. In the desire for two consecutive plantations during the water season, it causes the rural producer to neglect some agronomic practices that increase yields, especially when they arise from the increase in operational time.